2013
DOI: 10.1111/imj.12084
|View full text |Cite
|
Sign up to set email alerts
|

Review of medical discharge summaries and medical documentation in a metropolitan hospital: impact on diagnostic‐related groups and Weighted Inlier Equivalent Separation

Abstract: Comprehensive documentation of principal diagnosis/diagnoses, comorbidities and their complications is imperative to optimal DRG and WIES allocation. Regular meetings between clinical and coding staff improve the quality and timeliness of medical documentation, ensure adequate communication with general practitioners and lead to appropriate funding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 5 publications
(8 reference statements)
0
15
0
Order By: Relevance
“…Chin et al (2013) also reported the need for comprehensive documentation of principal diagnosis/es, co-morbidities and their complications to enable optimal DRG and WIES allocation in a Victorian hospital.…”
Section: Australian Researchmentioning
confidence: 99%
“…Chin et al (2013) also reported the need for comprehensive documentation of principal diagnosis/es, co-morbidities and their complications to enable optimal DRG and WIES allocation in a Victorian hospital.…”
Section: Australian Researchmentioning
confidence: 99%
“…Accurate and explicit medical note documentation by clinicians, as well as accurate coding inclusive of all AR‐DRG classifications, are vital for precise funding reimbursement and ongoing allocations, as well as epidemiological and research purposes. Poor medical note documentation can therefore inadvertently lead to incomplete AR‐DRG coding and suboptimal funding allocation . In our study, there was a significant proportion (81%) of encounters where additional diagnoses were captured.…”
Section: Discussionmentioning
confidence: 78%
“…In 2013, Chin et al . found that 48% of their 150 general medical inpatient admissions over a 3‐month period had DRG revisions, resulting in a financing consequence of AU$142 000 …”
Section: Discussionmentioning
confidence: 99%
“…This recommendation is supported by existing research. Quantitative research has shown that inaccurate discharge documentation leads to inaccuracies in hospital funding and increased health care costs . It also introduces serious risk and increases the chance of readmission .…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative research has shown that inaccurate discharge documentation leads to inaccuracies in hospital funding and increased health care costs. 49 It also introduces serious risk and increases the chance of readmission. 50 Clinical education and feedback for junior doctors increases the satisfaction of general practitioners and long-term/aged care facilities with the quality of discharge documenta-tion 51 and is viewed positively by participating interns and consultants.…”
Section: Feasibility Of a Self-directed Clinical Auditmentioning
confidence: 99%